Acute Extrapyramidal Side Effects from Smoked Haloperidol. (2nd October 2021) - Pham, Angeline; Lee, Joo-Young; Miller, Christopher W. T.
Abstract : Introduction . Haloperidol is a dopamine receptor antagonist used to treat patients with psychotic disorders. Especially at high doses, haloperidol carries a higher risk of extrapyramidal symptoms (EPS) compared to second-generation antipsychotics. Few cases of haloperidol misuse are found in the medical literature. Case Presentation . We describe a patient with schizophrenia who smoked marijuana mixed with crushed haloperidol tablets. After the smoking of cannabis and haloperidol, the patient presented to the emergency department (ED) with suicidal ideation, psychosis, and acute dystonia. With the administration of intramuscular diphenhydramine at the ED, the dystonia resolved in less than an hour. To our knowledge, this is the first report on haloperidol misuse by smoking. Conclusion . Clinicians should be aware that patients might misuse prescribed antipsychotics via unconventional routes, potentially combined with other substances.